(untitled) (LACCEI, 2024)
The present investigation was born from the need to increase the productivity of the box production line using engineering methods and tools, such as study of methods, study of times and line balance. The research approach was quantitative, with a non-applied scope, its level was descriptive-propositive and its design was non-experimental-transversal. The first thing to do was to determinate the productivity, prior to the proposal, of the stations, to later record the data, carry out studies of methods, times and line balancing. Subsequently, the improvement proposal was developed with the determination of roles, standard times and a work method, standardization of processes and the productivity of the proposal for each station was determined, calculating the respective financial evaluation. Finally, it was evidenced that the management proposal through the methods engineering theory in each station does generate a positive influence. In addition, it was verified that this proposal would be economically and financially viable, obtaining an IRR of 90.51%, a NPV of S/. 50,448.36 and a B/C that represents for each sol invested S/4.39 of profit